An unusual cause of haemoptysis: hepatobronchial fistula - Suman, Sonu (International Journal of Research in Medical Sciences, 2020)
Haemoptysis is a common clinical problem but a non-specific symptom and can occur in about 100 different clinical conditions. Diagnosing aetiology is not always straight forward. Authors present a case of Hepatobronchial fistula (HBF) which initially diagnosed as tuberculosis due to its atypical presentation and rarity of HBF.